2022
DOI: 10.1371/journal.pone.0262942
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium lactis BL-99 modulates intestinal inflammation and functions in zebrafish models

Abstract: This study was designed to explore the therapeutics and the mechanisms of a patented and marked gastric acid and intestine juice-resistant probiotics Bifidobacterium lactis BL-99 (B. lactis BL-99) on the intestinal inflammation and functions in the zebrafish models. After feeding for 6 hours, B. lactis BL-99 was fully retained in the larval zebrafish intestinal tract and stayed for over 24 hours. B. lactis BL-99 promoted the intestinal motility and effectively alleviated aluminum sulfate-induced larval zebrafi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…Bacillus coagulans 09•712 and Lactobacillus plantarum 08•923 showed robust zebrafish gut adhesion capability, and played immunoregulatory and immunoprotective roles in effective stimulation of anti-inflammatory response and barrier regeneration within the mucosa to protect zebrafish against infection (53). Bifidobacterium lactis BL-99 also could promote the intestinal integrity, improved the histopathology of the adult zebrafish intestinal inflammation, increased the goblet cell numbers, and recover microbiota metabolism to maintain intestinal health (54). Besides, several studies have found Pediococcus could exert beneficial effects in zebrafish (55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus coagulans 09•712 and Lactobacillus plantarum 08•923 showed robust zebrafish gut adhesion capability, and played immunoregulatory and immunoprotective roles in effective stimulation of anti-inflammatory response and barrier regeneration within the mucosa to protect zebrafish against infection (53). Bifidobacterium lactis BL-99 also could promote the intestinal integrity, improved the histopathology of the adult zebrafish intestinal inflammation, increased the goblet cell numbers, and recover microbiota metabolism to maintain intestinal health (54). Besides, several studies have found Pediococcus could exert beneficial effects in zebrafish (55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…Gene expressions were detected by qRT-PCR using iTaq Universal SYBR Green (Bio-Rad, Hercules, CA, USA) on the CFX Connect Real-Time PCR Detection System (Bio-Rad, CA, USA). The primer sequences were referred to other studies and listed in Table 1 [33][34][35][36][37][38][39][40][41]. The relative expression levels of the genes were normalized to β-actin and calculated using the 2 -ΔΔCT method.…”
Section: Quantitative Real-time-polymerase Chain Reaction (Qrt-pcr) A...mentioning
confidence: 99%
“…11 Then, it was con rmed that BL-99 could maintain intestinal health by reducing intestinal in ammation. 12 Moreover, recent studies suggested that BL-99 could utilize fructo-oligosaccharide (FOS) to regulate the composition and structure of gut microbiota in patients with constipation, thus promoting the production of short chain fatty acids (SCFAs). 13 Hence, the prolonged e cacy of BL-99 to improve FD symptoms and the underlying mechanism were explored by a pilot randomised, positive-drug and placebo-controlled trial.…”
Section: Introductionmentioning
confidence: 99%